2008
DOI: 10.1007/s11274-008-9821-4
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of arsenite-oxidizing bacteria from arsenic-contaminated soils in Thailand

Abstract: Two hundred and eighty-eight arsenic-resistant bacteria were isolated by an enrichment culture method from a total of 69 arsenic-contaminated soil-samples collected from Dantchaeng district in Suphanburi province (47 samples), and from Ron Phiboon district in Nakhon Sri Thammarat province (22 samples), in Central and Southern Thailand, respectively. Twenty-four of the 288 isolated arsenic-resistant bacteria were found to be arsenite-oxidizing bacteria. On the basis of their morphological, cultural, physiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…The main genus, Sphingomonas, comprises some heterotrophic species commonly found on contaminated sites, including sites polluted by metals (Beattie et al, 2018). They are able to degrade aromatic compounds (Fredrickson et al, 1995 ;Zylstra and Kim, 1997) and carry functional genes, such as the ars genes, linked to As resistance (Macur et al, 2001 ;Escalante et al, 2009) and the aioA genes linked to As oxidation (Kinegam et al, 2008). Other major heterotrophic genera, such as Pseudolabrys and Bryobacter, may contribute to the degradation of organic molecules initially present or provided with the organic litter during the mesocosm experiment.…”
Section: Microbial Community Structure 18mentioning
confidence: 99%
“…The main genus, Sphingomonas, comprises some heterotrophic species commonly found on contaminated sites, including sites polluted by metals (Beattie et al, 2018). They are able to degrade aromatic compounds (Fredrickson et al, 1995 ;Zylstra and Kim, 1997) and carry functional genes, such as the ars genes, linked to As resistance (Macur et al, 2001 ;Escalante et al, 2009) and the aioA genes linked to As oxidation (Kinegam et al, 2008). Other major heterotrophic genera, such as Pseudolabrys and Bryobacter, may contribute to the degradation of organic molecules initially present or provided with the organic litter during the mesocosm experiment.…”
Section: Microbial Community Structure 18mentioning
confidence: 99%
“…Through symbiotic network analysis, we found that Anaeromyxobacter (genus11) had a negative correlation with arsenate reductase (arsC, arsC1, and arsC2), which further confirmed that Astot has a negative impact on Proteobacteria. Geobacter [62], and Sphingomonas [63] were typical As metabolic bacteria. Sphingomonas had a positive response to As contamination fractions but had no response to Sb contamination fractions.…”
Section: Effects Of Bacterial Community On Sb and As Related Functionmentioning
confidence: 99%
“…Screening for As (III) oxidation and As (V) reduction activity The bacteria were tested on the ability to oxidize As (III) or reduce As (V) using a qualitative AgNO 3 screening method [10,11]. The bacteria were grown on nutrient broth with either 129.91 mg/L NaAsO 2 (sodium arsenite) or 312.01 mg/L Na 2 HAsO 4 (sodium arsenate).…”
Section: Sensitivity To Antibioticsmentioning
confidence: 99%
“…E. coli grow at 0.01 mM mercury concentration (a), 1 mM zinc concentration (b), and 1 mM nickel (c). Screening for As (III) oxidation and As (V) reduction activity The bacteria were tested on the ability to oxidize As (III) or reduce As (V) using a qualitative AgNO 3 screening method [10,11]. A light yellow color in mixtures containing arsenate indicates positive arsenate oxidation reaction (oxidation of the arsenate in the mixture to arsenite).…”
Section: Sensitivity To Antibioticsmentioning
confidence: 99%
See 1 more Smart Citation